(untitled) (Global Journal of Science Frontier Research, 2020)
The mathematical basics of graph paradigm programming of applied systems AS are presented The vertices of graph are been the functional modules of the systems and the arcs define the connections between them The graph is represented by an adjacency and reach ability matrix A number of graph program structures and their representation by mathematical operations unions connections differences etc are shown Given the characteristics of graph structures complexes units and systems created from the modules of the graph The method of modelling the system on the graph of modules which describe in the programming languages LP and the advanced operations of association link assembling make building config etc The standard of configuration 2012 Assembly of heterogeneous software elements in AS of different fields of knowledge is made A brief description of modern and future programming paradigms for formal theoretical creation of systems from intelligent and service-components of the Internet is given The modules and AS are protected and quality assessment There are giving the new direction of modern paradigms programming in the near future